The effect of freshwater acidification in the tissues of Cyprinus carpio - Ibrahim A; Narayanan M; Khan Salman; Sheik Mohamed (Global Journal of Zoology - Peertechz Publications, 2020)
The extant study was carried out to discern the effect of different acidic pH on the tissues of fishes. The experimental fish Cyprinus carpio were introduced into acidic waters (pH 5.0; 5.8; 6.6 and control 7.2) for 21 days for the histopathological exploration, the pH was upheld vigilantly throughout the investigation, after the experimental period, the results revealed the transfigures in the tissues of gills, intestine and liver. The annihilation of the epithelial layer with hypertrophy and hyperplasia in the gills and the development of necrotic gill disease, the fallouts from the intestine displayed the mucosal necrosis, and massive sloughing off mucosal epithelium, the liver unveiled the massive and intense granulomatous reaction and development of necrotic hepatitis.